Increasing Biogas Production Rate from Cattle Manure Using Rumen Fluid as Inoculums - Budiyono Budiyono; I Nyoman Widiasa; Seno Johari; S Sunarso (International Journal of Science and Engineering, 2014)
In this study, rumen fluid of animal ruminant was used as inoculums to increase biogas production rate from cattle manure at mesophilic condition. A series of laboratory experiments using 400 ml biodigester were performed in batch operation mode. Given 100 grams of fresh cattle manure (M) was fed to each biodigester and mixed with rumen fluid (R) and tap water (W) in several ratio resulting six different M:W:R ratio contents i.e. 1:1:0; 1:0.75:0.25; 1:0.5:0.5; 1:0.25:0.75; and 1:0:1 (correspond to 0; 12.5; 25, 37.5; 50, and 100 % rumen, respectively) and six different total solid (TS) contents i.e. 2.6, 4.6, 6.2, 7.4, 9.2, 12.3, and 18.4 %. The operating temperatures were at room temperature. The results showed that the rumen fluid inoculated to biodigester significantly effected the biogas production. Rumen fluid inoculums caused biogas production rate and efficiency increase more than two times in compare to manure substrate without rumen fluid inoculums. The best performance for biogas production was the digester with rumen fluid and TS content in the range of 25-50 % and 7.4 and 9.2 %, respectively. These results suggest that, based on TS content effects to biogas yield, rumen fluid inoculums exhibit the similar effect with other inoculums. Increasing rumen content will also increase biogas production. Due to the optimum total solid (TS) content for biogas production between 7-9 % (or correspond to more and less manure and total liquid 1:1), the rumen fluid content of 50 % will give the best performance for biogas production. The future work will be carried out to study the dynamics of biogas production if both the rumen fluid inoculums and manure are fed in the continuous system Doi: 10.12777/ijse.6.1.31-38 [How to cite this article: Budiyono, Widiasa, I.N., Johari, S. and Sunarso. (2014). Increasing Biogas Production Rate from Cattle Manure Using Rumen Fluid as Inoculums. International Journal of Science and Engineering, 6(1),31-38. Doi: 10.12777/ijse.6.1.31-38]